METHODOLOGICAL FOUNDATIONS OF INTERDISCIPINARY INTEGRATION IN THE TEACHING PRACTICE - Sukhodimtseva, Anna; Kirillova, Olga; Chemerilova, Irina; Lukashenko, Dmitry; Sergeeva, Marina (Revista Inclusiones, 2020)
Socio-economic and scientific integration profoundly affect the development of general education in Russia. The need for a school graduate to have a holistic picture of the world is one of the central issues facing Russian pedagogy and the research field of education. The issue of interdisciplinary integration has long been one of the core elements of educational policy in Russia and abroad. It is reflected in the educational standards and curricula of many countries and international organizations.